Effectiveness of Energy Efficiency Certificates as Drivers for Industrial Energy Efficiency Projects - Di Foggia, Giacomo (International Journal of Energy Economics and Policy, 2016)
The efficiency of policies in steering the implementation of energy efficiency projects has multiple implications including economic opportunity such as reduction of greenhouse gas emissions, security of supply, technological development opportunity for industry. One of the key new instruments foreseen to support energy efficiency improvements is the energy efficiency certificate (EEC). Focusing on the industrial business case, the purpose of this paper is twofold. First the energy performance contact is analyzed and discussed, second this paper shows how EECs concur in supporting the viability of the investment. Specifically, results suggest including this instrument the payback time reduction would be around 20% below the baseline hypothesis. Keywords: Energy efficiency certificates, energy efficiency, energy policy, payback time, EPC JEL Classifications: H3, L52, Q48